Precaution and risk aversion: Decomposing the effect of unemployment benefits on saving - Jonas Kolsrud (Uppsala University, Department of Economics, 2013)
Reduced form estimations of precautionary saving with respect to labor market risk have hitherto failed to consider that a decrease of say unemployment probability or an increase in unemployment insurance (UI) generosity affects saving not only by reducing the expected variance in earnings but also by raising expected earnings. This paper studies the possibility of decomposing the treatment effect of UI on asset accumulation into two parts; one part where more generous UI leads to raised expected earnings and a second part where a more generous UI reduces the expected variation in earnings. The decomposition is applied to rich Swedish register data on both financial assets and debt. UI's effect on assets is identified with a kinked policy rule in the UI scheme. First, increased UI generosity has a significant effect, both economically and statistically, on asset holdings; a one percentage point increase in UI benefits decrease net financial asset holdings by 1 percentage point. Second, decomposing the total effect UI has on asset accumulation shows that raised expected earnings increase savings while a decreased variation in earnings decrease saving. Not accounting for the effect on expected earnings on saving underestimates the impact UI has on precautionary saving by 70 percent.
urn:nbn:se:uu:diva-206018
Keywords: D91; J64; J65; 330; wealth; unemployment benefit; unemployment; consumption smoothing